2008
DOI: 10.1080/13647830802276131
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady simulation of a CO/H2/N2/air turbulent non-premixed flame

Abstract: The Sandia/ETH-Zurich CO/H 2 /N 2 non-premixed unconfined turbulent jet flame (named 'Flame A') is numerically simulated by solving the unsteady compressible reactive NavierStokes equations in a three-dimensional axisymmetric formulation, hence, in a formally twodimensional domain. The turbulent combustion closure model adopted is the Fractal Model, FM, developed as a subgrid scale model for Large Eddy Simulation. The fuel is injected from a straight circular tube and the corresponding Reynolds number is 16 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The SLF model (with a steady flamelet library of 20 different flamelets and different strain rates up to 1000 s −1 ) overpredicted the axial temperature profile, especially in the post-flame zone. Giacomazzi et al (2008) also performed axisymmetric simulations (of flame A) but using large eddy simulation (LES). They adopted the fractal model (FM) as a subgrid scale model.…”
Section: Introductionmentioning
confidence: 99%
“…The SLF model (with a steady flamelet library of 20 different flamelets and different strain rates up to 1000 s −1 ) overpredicted the axial temperature profile, especially in the post-flame zone. Giacomazzi et al (2008) also performed axisymmetric simulations (of flame A) but using large eddy simulation (LES). They adopted the fractal model (FM) as a subgrid scale model.…”
Section: Introductionmentioning
confidence: 99%
“…Equations (13 -14) are now closed requiring solutions given by known expressions. We assume that the flame behave as a fractal surface at all stages of its development [23,28,49,[54][55][56][57][58][59][60][61][62][63][64][65]:…”
Section: Definition Of a Model Problemmentioning
confidence: 99%
“…In the following, we assume that the flame behaves as a fractal surface at all stages of its development, as suggested by various models and analysis [23,28,49,[54][55][56][57][58][59][60][61][62][63][64][65]. Once derived the balance equations describing the evolution of a statistically one-dimensional flame evolving in an homogenous and isotropic frozen turbulence (Section 2), exact closures are proposed to fit this requirement (Section 3) while the influence of two sub-grid scale models, a simple algebraic model and its dynamic version, on resolved and total flame surfaces, and then on the overall turbulent flame speed, as well as the unsteady flame response, are discussed in Section 4, including model parameter uncertainties.…”
mentioning
confidence: 99%
“…Conversely, some previous studies have noted the influence of nonunity Lewis numbers. Giacomazzi et al , simulated a turbulent syngas jet flame considering nonunity Lewis numbers and reported that preferential mass diffusion of H 2 controlled flame stabilization near the nozzle. Meier et al also suggested that preferential mass diffusion played an important role, especially near the nozzle.…”
Section: Introductionmentioning
confidence: 99%